Functional and expression analysis reveals the involvement of integrin αvβ3 in antiviral immunity of grass carp (Ctenopharyngodon idella). Issue 129 (October 2022) - Xiong, Xiaoqing; Yang, Hong; Ding, Chunhua; Qin, Beibei; Deng, Yadong; Xiong, Liming; Liu, Xiaoyan; Li, Yaoguo; Xiao, Tiaoyi; Lv, Zhao
Abstract: Integrins are α-β heterodimeric cell receptors that can bind the protein components of pathogens, and play crucial roles in mammalian immune responses, but the immune functions mediated by integrins remains largely unknown in teleost fish. In this study, an integrin αvβ3 (GCαvβ3) originally assembled by αv (GCαv) and β3 (GCβ3) subunits, was identified from a teleost fish grass carp Ctenopharyngodon idella . The pairwise alignment analyses showed that the amino acid sequences of GCαv and GCβ3 shared high similarity (75.2–95.1%) and identity (58.6–90.7%) with their homologs from other vertebrates. Both GCαv and GCβ3 harbored the conserved protein domains and motifs, and were clustered in fish branch of the phylogenetic tree containing the counterparts from various vertebrates. Co-immunoprecipitation displayed that GCβ3 could interact with the grass carp reovirus (GCRV) outer capsid protein VP5. Two incubation experiments revealed that the interaction of GCRV or VP5 proteins with GCβ3 could induce the expressions of type I interferons (IFNs) including IFN2 and IFN3 in grass carp ovary cell line. The functional analysis demonstrated that GCαvβ3 served as a receptor of viral protein components to be involved in antiviral immunity as human integrin αvβ3 did. In addition, both GCαv and GCβ3 were significantly upregulated in various tissues of grass carp after GCRV infection. This study might provide fundamental basis for understanding the molecular characteristics and immune functions of GCαvβ3, and offer a new insight into the antiviral immune mechanism specific to the integrins in grass carp. Highlights: An integrin αvβ3 (GCαvβ3) was cloned and identified from grass carp. GCαvβ3 harbored the conserved protein domains and motifs as its homologs. GCαvβ3 could interact with the GCRV outer capsid protein VP5. GCαvβ3 could mediate the expressions of interferons during GCRV infection.